Determination of Bio Content in Polymers used in the Packaging of food Products. Issue 6 (5th December 2019) - Telloli, C; Rizzo, A; Canducci, C; Bartolomei, P
ABSTRACT: The ENEA Radiocarbon Laboratory (Bologna, Italy) has been operating since 1985; it is the oldest among such laboratories operating in Italy and has been active for about 30 years in the field of dating of different types of samples with the radiocarbon ( 14 C) liquid scintillation method. This study shows the detailed procedure for radiocarbon analysis on bioplastic materials by means of the synthesis of benzene, which includes CO2 production and purification, synthesis of acetylene, and synthesis and collection of benzene. The changes made to the original design of the synthesis procedures and the operational parameters adopted to optimize the combustion of the plastic materials are described. The measurement of 14 C activity was performed using the liquid scintillation counting technique by a Quantulus TM 1220 low-background counter. The δ 13 C content was compared with the percentage of 14 C concentration for the characterization of the bio content in plastic used in the food packaging.